Chilies Farmers’ Descriptive Thoughts on Importance of Agriculture Sustainability Practices - Nalini, Arumugam; Fakhrul Anwar, Zainol; Wan Norhayate, Wan Daud (2014)
This study is attempts to discover the importance of agriculture sustainability practices among chilies farmers from Malaysia East Coast Economic Region (ECER). A total of 199 chilies farmers were randomly selected. Data was collected using questionnaire as an instrument through face to face interview. The farmers rated the importance of each of the 35 selected sustainable agriculture practices on a 5-point likert like scale. The collected data was analyzed using SPSS v. 17.0. The mean score for each sustainable practice in term of importance derived. The most importance sustainable practice is “Land and water sources should be preserved”.There is need for more research in understanding these agriculture sustainability practices among other field agriculture farmers.